APLIKASI INTERPRETIVE STRUCTURAL MODELING (ISM) PADA FAKTOR-FAKTOR PENYEBAB KETERLAMBATAN PROYEK KONSTRUKSI DI SURABAYA - Eric Cahyadi Halim; Andi Andi; Jani Rahardjo (Program Studi Magister Teknik Sipil - Petra Christian University, 2021)
Construction projects run the risk of not conforming to the initial expectations of development. It is very difficult to estimate the time of a project because a project is not repetitive, there are different challenges in each development project. Delay in completing a project will cause waste in the form of overtime and overbudget. This research was conducted using judgment sampling to 5 respondents who were expert contractors. The objectives to be achieved through this research are to identify the dominant factors causing delays in a residental project using the Decision Making Trial and Evaluation Laboratory (DEMATEL) method and modeling the relationship between the factors that cause delays in residential construction projects using the Interpretive Structural Modeling (ISM) method. The result of this research is the existence of 8 levels of sub-factor hierarchical structure which becomes the framework for contractors and project owners to reduce the risk of delays in residential construction projects. The dominant causes of delays in project development are design changes during construction, late delivery of materials, late approval of work drawings, late payments, and inappropriate work methods.